STUDI ANTROPOLOGI AGAMA TENTANG PENGUATAN NILAI KEAGAMAAN SEBAGAI BASIS PENDIDIKAN KARAKTER DI LEMBAGA PENDIDIKAN ISLAM - Mahyuddin (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2022)
Strengthening religious values ​​as the basis for character education for the younger generation is important to do as an effort to overcome the polemic of moral degradation and identity crisis that overshadows students in the era of technological development. This study aims to describe the strengthening of religious values ​​among the younger generation in Islamic educational institutions so that they are able to become models in other educational institutions, especially in terms of developing students' character. This research is a type of qualitative research with a literature study and uses an anthropological approach to religion that focuses more on human, cultural and religious aspects. The data analysis technique in this study was started by categorizing research articles related to the research topic, then, analyzed using an anthropological approach. The results of this study indicate that efforts to strengthen religious values ​​as the basis for character education can be carried out by revitalizing institutional governance and orienting learning based on local cultural wisdom and contextual learning models.